2018
DOI: 10.1371/journal.pone.0208406
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular polymeric substances (EPS) producing and oil degrading bacteria isolated from the northern Gulf of Mexico

Abstract: Sinking marine oil snow was found to be a major mechanism in the transport of spilled oil from the surface to the deep sea following the Deepwater Horizon (DwH) oil spill. Marine snow formation is primarily facilitated by extracellular polymeric substances (EPS), which are mainly composed of proteins and carbohydrates secreted by microorganisms. While numerous bacteria have been identified to degrade oil, there is a paucity of knowledge on bacteria that produce EPS in response to oil and Corexit exposure in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 67 publications
2
20
0
Order By: Relevance
“…And they point out that Marinobacter and Alteromonas, Gammaproteobacteria, are common oil-degrading microorganisms. This result is in agreement with Bacosa et al 52 who analyzed the bacterial diversity of the same region and concluded that Alteromonas is an important class of bacteria in the fate of oil, being effective in degrading the alkanes in oil. Wang et al 53 studied the microbial community of oil-polluted soil on agricultural land in Fushun, Liaoning province in China, where they attested that the abundance of Enterobacteriales was greater in areas with oil-contaminated soil.…”
Section: Insupporting
confidence: 92%
“…And they point out that Marinobacter and Alteromonas, Gammaproteobacteria, are common oil-degrading microorganisms. This result is in agreement with Bacosa et al 52 who analyzed the bacterial diversity of the same region and concluded that Alteromonas is an important class of bacteria in the fate of oil, being effective in degrading the alkanes in oil. Wang et al 53 studied the microbial community of oil-polluted soil on agricultural land in Fushun, Liaoning province in China, where they attested that the abundance of Enterobacteriales was greater in areas with oil-contaminated soil.…”
Section: Insupporting
confidence: 92%
“…The main constituents of EPS, including polysaccharides, proteins, DNAs, lipids and other polymeric compounds, depend on the bacterial species, and the environmental conditions (Myszka and Czaczyk, 2009;Kostakioti et al, 2013;Limoli et al, 2015;Jayathilake et al, 2017;Bacosa et al, 2018;Costa et al, 2018). Polysaccharides are a major constituent of the EPS matrix and necessary for biofilm development and growth in most bacteria (Flemming et al, 2016).…”
Section: Eps Productionmentioning
confidence: 99%
“…The mucoid colonies have a glossy and slimy appearance on agar media were the primary criteria for selection of EPS-producing bacteria [33]. Earlier, the similar property of string formation and the mucoid colony has been reported by Bacosa et al [34] and Rühmann et al [28].…”
Section: Screening Of Eps-producing Coloniesmentioning
confidence: 74%